Intelligent, Automated, Rapid, and Safe Landmine, Improvised Explosive Device and Unexploded Ordnance Detection Using Maggy - Kaya Kuru (22282282) (2024)
Detecting and clearing legacy landmines, Improvised Explosive Devices (IED), and Unexploded Ordnances (UXO) using a force made up of humans or animals is extremely risky, labour- and time-intensive. It is crucial to quickly map millions of buried landmines/IDE/UXO, and remove them at a reasonable cost to minimise potential risks and make this labour-intensive task easier. Using unmanned vehicles and robots outfitted with various remote sensing modalities appears to be the ideal way to carry out this task in a non-invasive manner while employing a geophysical investigative method. In this study, a small-scale customised drone – the so-called Maggy – was developed to simplify and automate the procedures of cleaning explosive devices. It was instrumented with innovative intelligent automated techniques and magnetometer sensor technologies. Maggy’s performance was assessed in field tests conducted in Latvia and the United Kingdom. The outcomes, obtained in the open-air minefields and the benchmark assessments, verify the viability of the technologies, methods, and approaches integrated into Maggy for the efficient and economical detection of legacy landmines and IDE/UXO. This research provides the related research community with fundamental design and implementation parameters (e.g. flight speed, flight altitude) in building and using magnetometer-integrated Unmanned Aerial Systems (UAS). The improved versions of the developed easy-to-use compact technology are aimed to be deployed by humanitarian demining teams to expedite their clearing operations safely and efficiently. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2024.3493013